Evaluating the role of Section 1115 waivers on Medicaid coverage and utilization of opioid agonist therapy among substance use treatment admissions. (29th December 2019) - Tormohlen, Kayla N.; Krawczyk, Noa; Feder, Kenneth A.; Riehm, Kira E.; Crum, Rosa M.; Mojtabai, Ramin
Abstract: Objective: To examine the impact of Section 1115 waivers on Medicaid coverage and opioid agonist therapy (OAT) utilization among substance use treatment admissions. Data Source: Treatment Episode Data Set‐Admissions (TEDS‐A) (2001‐2012). Study Design: We examined effects of 1115 waiver implementation on proportions of substance use treatment admissions with Medicaid and receiving OAT, using random intercept linear regression. Principal Findings: 1115 waiver implementation was associated with an average of a 6 percentage point increase in proportion of all admissions with Medicaid, and 4 percentage point increase among opioid outpatient admissions. Implementation was not associated with change in proportion of opioid outpatient admissions receiving OAT. Conclusions: 1115 waivers influence Medicaid coverage among substance use treatment admissions. The findings improve our understanding of how state policies impact substance use treatment utilization.